Correlation of intra operative specimen imaging with final histopathology in breast conserving surgery for breast cancer - Nida Javed; Sidra Afzal; Muhammad Asad Parvaiz; Bushra Rehman; Ibtissam Bin Khalid (Journal of the Pakistan Medical Association)
Objectives: To determine the effectiveness of specimen mammography in breast conserving surgery cases with respect to reduction in margin positivity rate, and to see whether the rate of secondary surgeries is decreased by intra-operative excision based on specimen mammography evaluation.